Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Holocene overflow events of the lower Yellow River recorded in Huangdun ancient lake, northern Jiangsu Plain, China - Rui Zhang; Li Xing; Shi‐Yong Yu; Junsheng Nie; Jinjia Wu; Zhao Wang; Shiyue Chen; Zhanfang Hou; Guodong Zhang; Denghui Zhang (Journal of Quaternary Science, 2024)
Overflow events are important embodiments of the evolutionary characteristics of the lower Yellow River. Lakes in the lower reaches of the Yellow River have the capacity to record these events. Due to the complex provenance and transport pathways of sediments in local lakes, it is difficult to extract reliable information on sediments delivered by the Yellow River based on conventional methods and proxies. Here, we show results from a genetically meaningful end‐member (EM) decomposition of sediment grain‐size data from Huangdun ancient lake. The grain‐size of the sediments can be decomposed into three end‐members. Comprehensive analysis combining environmental magnetism and geochemical indicators clarifies the significance of each end‐member. EM1 represents mixed signals of various proximal fluvial sediments and the Yellow River materials. EM2 is similar to terrestrial fine‐grained debris in conjunction with local pedogenic materials, aeolian inputs and some Yi River materials. EM3 represents a component that is mainly derived from long‐distance transport by the lower Yellow River. End‐member analysis successfully identified overflow events of the lower Yellow River on a southward‐flowing path during the Holocene. This study provides a meaningful attempt to reconstruct the evolutionary history of the lower Yellow River from sedimentary records.

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

T4 ‐like myovirus community shaped by dispersal and deterministic processes in the South China Sea - Huifang Li; Lu Liu; Yu Wang; Lanlan Cai; Maoqiu He; Long Wang; Chen Hu; Nianzhi Jiao; Rui Zhang (Environmental Microbiology, 2021)
Summary As the most abundant and genetically diverse biological entities, viruses significantly influence ecological, biogeographical and evolutionary processes in the ocean. However, the biogeography of marine viruses and the drivers shaping viral community are unclear. Here, the biogeographic patterns of T4‐like viruses and the relative impacts of deterministic (environmental selection) and dispersal (spatial distance) processes were investigated in the northern South China Sea. The dominant viral operational taxonomic units were affiliated with previously defined Marine, Estuary, Lake and Paddy Groups. A clear viral biogeographic pattern was observed along the environmental gradient from the estuary to open sea. Marine Groups I and IV had a wide geographical distribution, whereas Marine Groups II, III and V were abundant in lower‐salinity continental or eutrophic environments. A significant distance‐decay pattern was noted for the T4‐like viral community, especially for those infecting cyanobacteria. Both deterministic and dispersal processes influenced viral community assembly, although environmental selection (e.g. temperature, salinity, bacterial abundance and community, etc.) had a greater impact than spatial distance. Network analysis confirmed the strong association between viral and bacterial community composition, and suggested a diverse ecological relationship (e.g. lysis, co‐infection or mutualistic) between and within viruses and their potential bacterial hosts.

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .